Abnormal Respiratory Symptoms of Workers and Sampling of Organic Vapors Using Solid-phase Microextraction Devices in a Golf Ball Manufacturing Factory - Wen-Hsi Cheng; Nai-Yu Chen (Aerosol and Air Quality Research)
Abstract The ink that is used in the mark printing, and the protective paints that are sprayed on golf balls as surface and primer layers are the main sources of volatile organic compounds (VOCs) in a golf ball manufacturing factory. In this investigation, workers’ exposures to VOCs were evaluated using a needle trap sampler (NTS), which is a micro sampling device, and the results of an analysis using a gas chromatography mass spectrometer were compared to the samples that were collected in charcoal adsorption tubes with respect to VOC content. Ethyl acetate and n-butyl acetate are main compounds that are emitted in the painting and printing of golf ball. The highest worker time weighted average exposure concentration of n-butyl acetate was 16.92 ppm, and that for ethyl acetate was 19.69 ppm, as measured in a closed spray room. Painters’ and printers’ symptoms of respiratory tract abnormalities (RTA) were strongly correlated with their exposures to organic solvents as determined from the answers to a questionnaire survey on workers’ RTA symptoms. An NTS can be used as an alternative to charcoal tubes for sampling organic solvents to which workers are exposed, based on the differences in the limiting VOC analysis concentrations of both sampling devices. Due to lighter weight and lower cost than the traditional charcoal tube, which has to be connected to a sampling pump, therefore, NTS should be promoted as a routine VOC monitoring device in the workplace.